A Deterministic Method to Construct a Common Supercell Between Two Similar Crystalline Surfaces - Lee, WeonGyu; Lee, JungHoon (WILEY-V C H VERLAG GMBH, 2024)
Here, a deterministic algorithm is proposed, that is capable of constructing a common supercell between two similar crystalline surfaces without scanning all possible cases. Using the complex plane, the 2D lattice is defined as the 2D complex vector. Then, the relationship between two surfaces becomes the eigenvector？eigenvalue relation where an operator corresponds to a transformation matrix. It is shown that this transformation matrix can be directly determined from the lattice parameters and rotation angle of the two given crystalline surfaces with O(log？Nmax) time complexity, where Nmax is the maximum index of repetition matrix elements. This process is much faster than the conventional brute force approach ( ). By implementing the method in Python code, experimental 2D heterostructures and their moir？ patterns and additionally find new moir？ patterns that have not yet been reported are successfully generated. According to the density functional theory (DFT) calculations, some of the new moir？ patterns are expected to be as stable as experimentally-observed moir？ patterns. Taken together, it is believed that the method can be widely applied as a useful tool for designing new heterostructures with interesting properties.